1980
DOI: 10.1038/286625a0
|View full text |Cite
|
Sign up to set email alerts
|

Chemically induced myotonia in amphibia

Abstract: Frogs and toads treated with high doses of anthracene-9-carboxylic acid (A-9-C) develop prolonged muscular contractions and 'divebomber' electromyograms characteristic of myotonia. Hitherto, myotonia has been considered peculiar to homeotherms where it is associated with several hereditable diseases and can be induced by specific treatments, most of which seem to act by decreasing membrane chloride conductance. Our work indicates that myotonia can be induced in amphibia by similar means. We offer possible reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Mammalian, but not amphibian, skeletal muscle fibres possess a large t-tubular G Cl (Dulhunty, 1979). Moreover, considerably higher doses and longer exposures to 9AC are required to induce myotonic behaviour in frogs compared to mammals (Bretag et al 1980), suggesting that frogs have a reduced sensitivity to 9AC. These data raise the possibility that the effects of extracellular ATP on mammalian skeletal muscle might be less pronounced or even absent at the frog NMJ.…”
Section: Figure 7 P2y 1 Receptor Identification and Maximum Effectmentioning
confidence: 99%
“…Mammalian, but not amphibian, skeletal muscle fibres possess a large t-tubular G Cl (Dulhunty, 1979). Moreover, considerably higher doses and longer exposures to 9AC are required to induce myotonic behaviour in frogs compared to mammals (Bretag et al 1980), suggesting that frogs have a reduced sensitivity to 9AC. These data raise the possibility that the effects of extracellular ATP on mammalian skeletal muscle might be less pronounced or even absent at the frog NMJ.…”
Section: Figure 7 P2y 1 Receptor Identification and Maximum Effectmentioning
confidence: 99%
“…5B, the residual outward current still rose at the end of the ON segment even though the duration of the TEST pulse was doubled. The retardation caused by 9-ACA made it difficult to quantify the fraction of the Cl-current that disappeared, especially since Bretag, Dawe & Moskwa (1980) reported that 9-ACA is much less potent in blocking Cl-current in amphibian muscle than in mammalian muscle. Prolonging the TEST pulses further generated movement artifacts, even in fibres stretched to a 4 4um sarcomere length.…”
Section: Anions As Carriers For the Delayed Outward Ionic Currentmentioning
confidence: 99%
“…The obvious approach is a mathematical in silico approach, modeling muscular excitation that takes into account both the reduction in chloride conductance (or, conversely, Na v channel gain‐of‐function) and the reduction in available Na v channels during slow‐inactivation . These analyses could be backed up by myotonia animal models, chemical (e.g., the 9‐anthracene carboxylic acid) or genetic (e.g., the ADR mouse), in which slow‐inactivation is pharmacologically enhanced, such as through administration of lacosamide or rufinamide. The slow‐inactivation/warm‐up hypothesis would also be supported if sodium channel myotonia mutations were identified that carry with them severely compromised slow‐inactivation.…”
Section: The Warm‐up Phenomenonmentioning
confidence: 99%